Physical activity, sport and transnational migrant spaces in Shanghai, China: (Re)crafting contours of a metropolitan cityscape. (March 2022) - Kohe, Geoffery Zain; Nehring, Daniel; Tu, Mengwei
This study examines associations between sport/physical activity space, community formation and social life among Shanghai's highly skilled migrant demographic. There is limited illustration of the roles sport and physical exercise provision and spaces play in this migrant cohort's lives, community formation and participation in their host societies. Yet, such evidence is of value in determining social policy, urban development and community engagement initiatives. Using a mixed-methods approach involving public policy critique, cultural and spatial analysis and virtual community investigation, this article provides a conceptual exploration of ways sport and physical activity frame individual and collective migrant experiences, and how such experiences enmesh with wider geo-spatial, political and domestic context. Amid Shanghai's presentation as a globally attractive space, we reveal some of the complexities of the cityscape as an emblematic location for highly mobile, highly skilled migrants. A confluence of ideals about urban citizenship, social participation and localised physical activity/sport-based (inter)action, we note, articulate Shanghai anew, and contribute to debates on highly skilled transnational mobility and community formation.